POWER RELATIONS OF THE PARTICIPANTS OF THE EDUCATIONAL PROCESS AND THEIR TRANSFORMATION IN THE PERSPECTIVE OF THE LEARNING PARADIGM - Lenkauskaitė, Jurgita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article deals with the problems of the power relations of the participants of the educational process. In the educational process, power is usually demonstrated not directly, but it is expressed employing rituals, rules, subtle control mechanisms, etc. Traditional teaching forms and methods, focused on the transferring of knowledge, help to maintain hierarchical relations in the educational process. The scientists (Duoblienė, 2009) notice that it is not possible to avoid power relations, but they can be reflected on. In the context of education, it foresees the perspective of the change in critical thought and power relations. The shift from the teaching paradigm to the learning paradigm is related to the possibility to recognize the expression of power relations and replace the traditional educational practice with a new one, that reflects the activity and equality of all the participants of the educational process. The aim of the research is to reveal the expression of power relations of the participants of the educational process and reflect on the situation of their transformation that occurs in the perspective of the learning paradigm. Problem questions: How do power relations manifest themselves in the educational process? How do they change while moving from the teaching paradigm to the learning paradigm? The methods of the analysis of scientific literature and written reflection by pedagogues have been applied in the research. The analysis of scientific literature presupposed the possibility to reveal the expression of power relations of the participants of the educational process, the implicit character of power relations and the situation of their change in the perspective of the learning paradigm. Written reflection by pedagogues reveals their efforts of critical thinking recognizing power relations in the context of their professional activity, analysing the causes of these relations and the potential of their change.